2021
DOI: 10.1007/s13238-021-00841-y
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis, radiotherapy, and combination therapeutic strategies

Abstract: Ferroptosis, an iron-dependent form of regulated cell death driven by peroxidative damages of polyunsaturated-fatty-acid-containing phospholipids in cellular membranes, has recently been revealed to play an important role in radiotherapy-induced cell death and tumor suppression, and to mediate the synergy between radiotherapy and immunotherapy. In this review, we summarize known as well as putative mechanisms underlying the crosstalk between radiotherapy and ferroptosis, discuss the interactions between ferrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
162
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(179 citation statements)
references
References 190 publications
2
162
0
Order By: Relevance
“…Ferroptosis is a recently discovered type of regulated cell death (RCD) that differs morphologically, biochemically, and genetically from apoptosis, autophagy, and necrosis and is characterized by iron-dependent and lethal reactive oxygen species (ROS) and lipid peroxidation(LPO) accumulation [9,10]. In recent years, inducing ferroptosis in cancer cells become a latent target for cancer therapy [11][12][13], especially in those drug-tolerant and radiation resistant cancers [14,15]. Previous studies have also demonstrated that ferroptosis plays important roles in OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Ferroptosis is a recently discovered type of regulated cell death (RCD) that differs morphologically, biochemically, and genetically from apoptosis, autophagy, and necrosis and is characterized by iron-dependent and lethal reactive oxygen species (ROS) and lipid peroxidation(LPO) accumulation [9,10]. In recent years, inducing ferroptosis in cancer cells become a latent target for cancer therapy [11][12][13], especially in those drug-tolerant and radiation resistant cancers [14,15]. Previous studies have also demonstrated that ferroptosis plays important roles in OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Growing evidence also reveals that ferroptosis (at least partially) contributes to the anti-cancer therapeutic effects of common cancer therapies, including radiotherapy, targeted therapies, and immunotherapy. [28][29][30][31][32][33] Importantly, cancer cells in specific cell states (such as drug-tolerant persister cancer cells or those in therapyresistant state) [34,35] or harboring certain mutations (such as mutations in E cadherin-NF2-Hippo pathway [36] ) are vulnerable to ferroptosis. Therefore, targeting ferroptosis has emerged as a promising therapeutic strategy for treating certain cancers.…”
Section: Instead Incorporation Of Mufas Into Pls Can Displace Pufas Frommentioning
confidence: 99%
“…Recently, the stimulation of ferroptosis has mushroomed as an alternative therapeutic approach to tumor suppression, especially for therapy-resistant patients (Hassannia et al, 2019;Liang et al, 2019). Ferroptosis exerts effectiveness in radiotherapy-induced cancer suppression and mediates the synergy of radiation therapy and immunotherapy (Lei et al, 2021). Apart from drivers and inducers of ferroptosis, many genes have been defined as suppressors, inhibitors, markers, and ferroptosis-disease associations (Zhou and Bao, 2020).…”
Section: Introductionmentioning
confidence: 99%